2019
DOI: 10.1002/joc.6372
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of COSMO‐CLM regional climate model in simulating precipitation over Central Africa

Abstract: In this study, an analysis of present day climate simulation (1998–2008) is presented for the Central African (CA) region with the COnsortium for Small‐scale MOdelling in CLimate Mode (CCLM) regional climate model, forced by the ERA‐Interim (ERAINT) reanalysis data. The ability of the CCLM to simulate the observed precipitation with particular focus on the mean spatial pattern, low‐level circulation, seasonal cycles, and daily characteristics is evaluated. Likewise, the added value of the regional model CCLM c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…However, there are notable differences in the frequency of rainy days among observations. Previous studies have confirmed discrepancies in extreme precipitation for gridded observational datasets over Africa (Sylla et al ., 2013; Pinto et al ., 2016; Fotso‐Kamga et al ., 2020). These studies attributed discrepancies among observations to various factors (e.g., differences in spatial resolution across observations; merging and interpolation techniques).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are notable differences in the frequency of rainy days among observations. Previous studies have confirmed discrepancies in extreme precipitation for gridded observational datasets over Africa (Sylla et al ., 2013; Pinto et al ., 2016; Fotso‐Kamga et al ., 2020). These studies attributed discrepancies among observations to various factors (e.g., differences in spatial resolution across observations; merging and interpolation techniques).…”
Section: Resultsmentioning
confidence: 99%
“…These downscaling experiments, which have been performed over the African continent at a horizontal resolution of 50km (∼0.44°), cover the period from 1950 to 2100 and have been forced by the higher GHG representative concentration pathways scenario (RCP8.5; Moss et al, 2010). Most of these RCMs have recently been extensively validated in previous studies conducted over Central Africa (Fotso‐Nguemo et al, 2016; Pokam et al, 2018; Tamoffo et al, 2019; Fotso‐Nguemo et al, 2019; Taguela et al, 2020; Fotso‐Kamga et al, 2020). They conclude that not only does the model bias vary with respect to season and the considered subregion but also that the multi‐model ensemble mean outperforms any individual models.…”
Section: Study Area Data Used and Methodologymentioning
confidence: 99%
“…In particular, investigations of processes regulating the energy balance that raises the near-surface temperature, rather than focusing only on processes explaining rainfall bias in models in particular over Central Africa (e.g. Dommo et al 2018;Fotso-Kamga et al 2020, Fotso-Nguemo et al 2016, 2017Washington 2018, 2019;Tamoffo et al 2019Tamoffo et al , 2021aTaguela et al 2020Taguela et al , 2022a. These surface thermal processes depend strongly on insolation, vegetation cover and albedo.…”
Section: Heat Lows and Jets Strength In Modelsmentioning
confidence: 99%